Analysis of Wind Energy Potential On Nusa Penida Island Using The Weibull Distribution: Evaluation of Power Density and Intermittency - Herlambang, Amanda Austin; Dewi Wirastuti, Ni Made Ary Esta; Manuaba, Ida Bagus Gede (Faculty of Engineering, Universitas Tanjungpura, 2025)
Nusa Penida Island faces increasing energy demands driven by tourism and development, highlighting the need for sustainable energy solutions. While previous wind studies in Indonesia have primarily focused on larger islands, this research evaluates Nusa Penida